Four new species and a new record of Anaedus from China (Coleoptera: Tenebrionidae) - Wang, Feng-Yan; Ren, Guo-Dong (Zootaxa, 2007)
Four new species of Anaedus Blanchard, A. unidentatus sp. nov., A. tibiodentatus sp. nov., A. basilatilus sp. nov., and A. pluridentatus sp. nov. are described. Anaedus mroczkowskii Kaszab, 1968 is newly recorded from China.